2021
DOI: 10.1002/ange.202101571
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Negishi Coupling between Organozinc Compounds and (Hetero)Aryl Bromides under Aerobic Conditions when using Bulk Water or Deep Eutectic Solvents with no Additional Ligands

Abstract: Pd‐catalyzed Negishi cross‐coupling reactions between organozinc compounds and (hetero)aryl bromides have been reported when using bulk water as the reaction medium in the presence of NaCl or the biodegradable choline chloride/urea eutectic mixture. Both C(sp3)‐C(sp2) and C(sp2)‐C(sp2) couplings have been found to proceed smoothly, with high chemoselectivity, under mild conditions (room temperature or 60 °C) in air, and in competition with protonolysis. Additional benefits include very short reaction times (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Knochel and co‐workers have introduced organozinc pivalates RZnOPiv⋅Mg(OPiv)Cl⋅ n LiCl (Piv=C(O) t Bu) as a new class of reagents, which can be handled under air for a short time [5] . Perhaps even more remarkably, the groups of Lipshutz and Capriati have shown that palladium‐catalyzed cross‐coupling reactions of organozinc reagents with various organyl halides selectively and efficiently proceed in water and other protic media in the presence of additives, such as N , N , N ′, N ′‐tetramethylethylenediamine or simple alkali‐metal salts [6,7] . These results imply that the coupling reactions successfully compete with the hydrolysis of the organozinc reagents, in spite of the high basicity of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Knochel and co‐workers have introduced organozinc pivalates RZnOPiv⋅Mg(OPiv)Cl⋅ n LiCl (Piv=C(O) t Bu) as a new class of reagents, which can be handled under air for a short time [5] . Perhaps even more remarkably, the groups of Lipshutz and Capriati have shown that palladium‐catalyzed cross‐coupling reactions of organozinc reagents with various organyl halides selectively and efficiently proceed in water and other protic media in the presence of additives, such as N , N , N ′, N ′‐tetramethylethylenediamine or simple alkali‐metal salts [6,7] . These results imply that the coupling reactions successfully compete with the hydrolysis of the organozinc reagents, in spite of the high basicity of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…n-Hexane was dried with molecular sieves and used without further purification. 1 H and 13 C NMR spectra were recorded on Bruker Advance III 400 MHz or Bruker Avance III 700 MHz instruments at ambient temperature. Chemical shifts are reported in parts per million (d scale), and coupling constants (J values) are given in Hertz.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…90 The judicious addition of water to some DESs can expand their liquidus range and enhance their processability by lowering the viscosity while providing catalytic activity and a suitable environment for certain reactions. [166][167][168] Graphene-related, 169 carbon nanotubes 45 and other carbonaceous materials have been demonstrated to serve as reinforcements of wearable electronics while improving the electrical conductivity if percolation throughout the matrix is achieved. Conductive polymers, such as polyaniline, 42 poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), polypyrrole, 170 and poly(3-octylthiophene), 43 can contribute to conductivity in energy-related applications 171 when biodegradability is not the central matter but biocompatibility is required.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%